Activation of locus coeruleus-spinal cord noradrenergic neurons alleviates neuropathic pain in mice via reducing neuroinflammation from astrocytes and microglia in spinal dorsal horn - Li, Juan; Wei, Yiyong; Zhou, Junli; Zou, Helin; Ma, Lulin; Liu, Chengxi; Xiao, Zhi; Liu, Xingfeng; Tan, Xinran; Yu, Tian; Cao, Song (Journal of neuroinflammation, 2022)
Background The noradrenergic neurons of locus coeruleus (LC) project to the spinal dorsal horn (SDH), and release norepinephrine (NE) to inhibit pain transmission. However, its effect on pathological pain and the cellular mechanism in the SDH remains unclear. This study aimed to explore the analgesic effects and the anti-neuroinflammation mechanism of LC-spinal cord noradrenergic pathway (LC:SC) in neuropathic pain (NP) mice with sciatic chronic constriction injury. Methods The Designer Receptors Exclusively Activated by Designer Drugs (DREADD) was used to selectively activate LC:SC. Noradrenergic neuron-specific retro–adeno-associated virus was injected to the spinal cord. Pain threshold, LC and wide dynamic range (WDR) neuron firing, neuroinflammation (microglia and astrocyte activation, cytokine expression), and α2AR expression in SDH were evaluated. Results Activation of LC:SC with DREADD increased the mechanical and thermal nociceptive thresholds and reduced the WDR neuron firing. LC:SC activation (daily, 7 days) downregulated TNF-α and IL-1β expression, upregulated IL-4 and IL-10 expression in SDH, and inhibited microglia and astrocytes activation in NP mice. Immunofluorescence double staining confirmed that LC:SC activation decreased the expression of cytokines in microglia of the SDH. In addition, the effects of LC:SC activation could be reversed by intrathecal injection of yohimbine. Immunofluorescence of SDH showed that NE receptor α2B-AR was highly expressed in microglia in CCI mice. Conclusion These findings indicate that selective activation of LC:SC alleviates NP in mice by increasing the release of NE and reducing neuroinflammation of astrocytes and microglia in SDH.